CGIAR researchfordevelopment program on mycotoxins - Ortíz, R.; Ban, T.; Bandyopadhyay, Ranajit; Bänziger, Marianne; Bergvinson, David; Hell, K.; James, B.; Jeffers, D.; Kumar, L.; Menkir, A.; Murakami, J.; Nigam, S.; et al. (CAB International, 2008)
The major mycotoxins studied at the Consultative Group on International Agricultural Re-search (CGIAR) institutes are aflatoxins in maize, groundnut, sorghum and cassava, Fusa-rium toxins in maize, wheat and sorghum, and ochratoxin in cocoa and cashew. Genetic en-hancement (both through plant breeding and biotechnology), biological control, habitat man-agement, risk assessment, institutional capacity building and public awareness are among the tools in the “CGIAR research-for-development kit” to fight mycotoxins worldwide. A holistic approach should be pursued to deal with mycotoxins that includes the following elements: i) an integrated crop management package that combines mycotoxin-resistant germplasm, bio-logical control, habitat control and soil-amendments; ii) low-cost mycotoxin detection tech-nology for rapid appraisal that also should facilitate trade; iii) a participatory process for my-cotoxin assessment in commercially important crops; and iv) a high-level panel composed of scientists, NGOs, farmers, traders, consumers, health officers and policy makers to monitor mycotoxin intervention strategies and to organize awareness campaigns.